STRATEGI PENGEMBANGAN USAHA KEDAI KOPI GARASI IPOK DI DISTRIK MNAOKWARI BARAT KABUPATEN MANOKWARI - Aloysia Florida Jamlean; Atmodjo, Ery; Maria Irene Arim (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2024)
Garasi Ipok coffee shop is a coffee shop in West Manokwari District, Manokwari Regency which has a quite strategic location. The aim of this research is to analyze internal and external business factors and formulate business development strategies. The method used in this research is descriptive with a case study approach using SWOT analysis. The data sources used in this research are primary and secondary data. Primary data was obtained from observations and interviews based on questionnaire. The results of the SWOT analysis shows that Kedai Kopi Garasi Ipok is in a very profitable situation. The Coffee shop has strengths internally and opportunities externally. The development strategy that can be implemented by the coffe shop is aggressive growth (growth-oriented strategy).